A computational overview on phylogenetic characterization, pathogenic mutations, and drug targets for Ebola virus disease. (December 2021) - Vasudevan, Karthick; Thirumal Kumar, D.; Udhaya Kumar, S.; Saleem, Aisha; Nagasundaram, N.; Siva, R.; Tayubi, Iftikhar Aslam; George Priya Doss, C.; Zayed, Hatem
Abstract: The World Health Organization declared Ebola virus disease (EVD) as the major outbreak in the 20th century. EVD was first identified in 1976 in South Sudan and the Democratic Republic of the Congo. EVD was transmitted from infected fruit bats to humans via contact with infected animal body fluids. The Ebola virus (EBOV) has a genome size of ∼18, 959 bp. It encodes seven distinct proteins: nucleoprotein (NP), glycoprotein (GP), viral proteins VP24, VP30, VP35, matrix protein VP40, and polymerase L is considered a prime target for potential antiviral strategies. The current US FDA-approved anti-EVD vaccine, ERVERBO, and the other equally effective anti-EBOV combinations of three fully human monoclonal antibodies such as REGN-EB3, primarily target the envelope glycoprotein. This work elaborates on the EBOV's phylogenetic structure and the crucial mutations associated with viral pathogenicity. Highlights: Phylogenetic characterization of Ebola virus. Naturally occurring mutations A82V, R111C, and D759G. Strucutural features and replication of Ebola virus. Strucural targets and computational drug design for Ebola Virus disease (EVD).